2019
DOI: 10.5194/amt-12-4039-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ground-based and satellite measurements of water vapour vertical profiles over Ellesmere Island, Nunavut

Abstract: Abstract. Improving measurements of water vapour in the upper troposphere and lower stratosphere (UTLS) is a priority for the atmospheric science community. In this work, UTLS water vapour profiles derived from Atmospheric Chemistry Experiment (ACE) satellite measurements are assessed with coincident ground-based measurements taken at a high Arctic observatory at Eureka, Nunavut, Canada. Additional comparisons to satellite measurements taken by the Atmospheric Infrared Sounder (AIRS), Michelson Interferometer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…This low bias is further reflected in climatological studies involving MAESTRO ozone, such as that of Hegglin et al (2021), who found low biases of around 50 % in the upper troposphere and 10 %-20 % in the lower stratosphere, except for the tropics where it had a high bias of about 20 % compared to a multi-instrument mean ozone climatology. In terms of water vapour, Weaver et al (2019) found that the previous version of MAESTRO water vapour, v30, was biased low by 6 %-12 % in the upper troposphere and by less than 2 % in the lower stratosphere as compared to measurements from the PEARL FTIR. As compared to radiosondes, MAESTRO had a mean upper tropospheric bias of between 16 % and 64 % but a lower stratosphere bias of less than 3 % (Weaver et al, 2019).…”
Section: Ace-maestromentioning
confidence: 80%
See 2 more Smart Citations
“…This low bias is further reflected in climatological studies involving MAESTRO ozone, such as that of Hegglin et al (2021), who found low biases of around 50 % in the upper troposphere and 10 %-20 % in the lower stratosphere, except for the tropics where it had a high bias of about 20 % compared to a multi-instrument mean ozone climatology. In terms of water vapour, Weaver et al (2019) found that the previous version of MAESTRO water vapour, v30, was biased low by 6 %-12 % in the upper troposphere and by less than 2 % in the lower stratosphere as compared to measurements from the PEARL FTIR. As compared to radiosondes, MAESTRO had a mean upper tropospheric bias of between 16 % and 64 % but a lower stratosphere bias of less than 3 % (Weaver et al, 2019).…”
Section: Ace-maestromentioning
confidence: 80%
“…In terms of water vapour, Weaver et al (2019) found that the previous version of MAESTRO water vapour, v30, was biased low by 6 %-12 % in the upper troposphere and by less than 2 % in the lower stratosphere as compared to measurements from the PEARL FTIR. As compared to radiosondes, MAESTRO had a mean upper tropospheric bias of between 16 % and 64 % but a lower stratosphere bias of less than 3 % (Weaver et al, 2019). The global comparisons of MAESTRO v31 water vapour against an ensemble of instruments, as performed by Lossow et al (2019), indicate that the MAESTRO bias is roughly parabolic with altitude.…”
Section: Ace-maestromentioning
confidence: 80%
See 1 more Smart Citation
“…The PEARL Ridge Lab is a remote site and is minimally influenced by local pollution sources. The PEARL-FTS was installed in July 2006, has been involved in the annual Canadian Arctic ACE-OSIRIS Validation Campaigns held during polar sunrise since spring 2007, and has been previously compared with ACE-FTS and other satellite-borne in-struments: for example, Clerbaux et al (2008), Batchelor et al (2010), Holl et al (2016), Buchholz et al (2017, Griffin et al (2017), Olsen et al (2017), Bognar et al (2019), Weaver et al (2019), andVigouroux et al (2020).…”
Section: Pearl-ftsmentioning
confidence: 99%
“…The ground-based instrument used in this study is a Bruker IFS 125HR Fourier transform spectrometer located at the Polar Environment Atmospheric Research Laboratory Ridge Laboratory (80.05°N, 86.42°W; 610 m ASL) in Eureka, Nunavut, Canada (Batchelor et al, 2009). The PEARL Ridge Laboratory is operated by the Canadian Network for the Detection of Atmospheric Change (CANDAC), and is situated approximately 15 km away from the Environment and Climate Change Canada (ECCC) Eureka Weather Station (79.98°N, 85.93°W; 0 m ASL) (Fogal et al, 2013 Batchelor et al (2010), Holl et al (2016), Buchholz et al (2017), Griffin et al (2017), Olsen et al (2017), Bognar et al (2019), Weaver et al (2019), andVigouroux et al (2020).…”
Section: Pearl-ftsmentioning
confidence: 99%